2006
DOI: 10.1111/j.1469-0691.2006.01447.x
|View full text |Cite
|
Sign up to set email alerts
|

A community outbreak of Legionnaires' disease: evidence of a cooling tower as the source

Abstract: A community outbreak of Legionella pneumonia in the district of Cerdanyola, Mataró (Catalonia, Spain) was investigated in an epidemiological, environmental and molecular study. Each patient was interviewed to ascertain personal risk-factors and the clinical and epidemiological data. Isolates of Legionella from patients and water samples were subtyped by pulsed-field gel electrophoresis. Between 7 August and 25 August 2002, 113 cases of Legionella pneumonia fulfilling the outbreak case definition criteria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 23 publications
3
42
0
2
Order By: Relevance
“…About one-half of them have been associated with human Legionnaires' disease (20), which occurs after inhalation of aerosolized water contaminated with virulent Legionella strains. Numerous cases of legionellosis after exposure to contaminated water from the water distribution systems of hotels, hospitals, and cooling towers have been reported (8,9,36). The major reservoirs of Legionella spp.…”
mentioning
confidence: 99%
“…About one-half of them have been associated with human Legionnaires' disease (20), which occurs after inhalation of aerosolized water contaminated with virulent Legionella strains. Numerous cases of legionellosis after exposure to contaminated water from the water distribution systems of hotels, hospitals, and cooling towers have been reported (8,9,36). The major reservoirs of Legionella spp.…”
mentioning
confidence: 99%
“…L. pneumophila is more frequently isolated from man-made water systems with high water temperature (9,17) than from relatively cold freshwater environments (4,16). This fact suggests that thermal conditions affect the relationship between L. pneumophila and protozoa, a notion supported by some reports (1,3,7,11).…”
mentioning
confidence: 99%
“…Despite genetic variability, in small geographical areas the same indistinguishable pulsed-field gel electrophoresis patterns may be shared among different cooling towers and persist over time.The involvement of cooling towers in some community outbreaks of legionellosis has been demonstrated (3,6,8,9,11), and it has been suggested that there may be an association between high Legionella counts in cooling towers and the occurrence of an outbreak of legionellosis (12). Although not all environmental isolates are associated with human disease, the present guidelines aimed at preventing legionellosis have proposed ranges of risk involving different environmental insults based on Legionella counts (4).…”
mentioning
confidence: 99%